Horton Foote : a literary biography - Watson, Charles S., 1931- (Jack and Doris Smothers series in Texas history, life, and culture ;, 2003)
"Winner of the Pulitzer Prize for Drama for The Young Man from Atlanta and Academy Awards for the screen adaptation of To Kill a Mockingbird and the original screenplay Tender Mercies, as well as the recipient of an Academy Award nomination for the screenplay of The Trip to Bountiful and the William Inge Lifetime Achievement Award, Horton Foote is one of America's most respected writers for stage and screen. The deep compassion he shows for his characters, the moral vision that infuses his social commentary, and the kindness and humanity that Foote himself radiates have also made him one of our most revered artists--the father-figure who understands our longings for home, for human connections, and for certainty in a world largely bereft of these.This literary biography thoroughly investigates how Horton Foote's life and worldview have shaped his works for stage, television, and film. Tracing the whole trajectory of Foote's career from his small-town Texas upbringing to the present day, Charles Watson demonstrates that Foote has created a fully imagined mythical world from the materials supplied by his own and his family's and friends' lives in Wharton, Texas, in the early twentieth century. Devoting attention to each of Foote's major works in turn, he shows how this world took shape in Foote's writing for the New York stage, Golden Age television, Hollywood films, and in his nine-play masterpiece, The Orphan's Home Cycle. Throughout, Watson's focus on Foote as a master playwright and his extensive use of the dramatist's unpublished correspondence make this literary biography required reading for all who admire the work of Horton Foote."